Bohemians, human capital, and regional economic growth - Oliver Falck; Michael Fritsch; Stephan Heblich (Center for Economic Studies and ifo Institute (CESifo), 2009)
An emerging literature on the geography of bohemians argues that a region's lifestyle and cultural amenities explain, at least partly, the unequal distribution of highly qualified people across space, which in turn, explains geographic disparities in economic growth. However, to date, there has been little or no empirical attempt to identify a causal relation. To identify the causal impact of bohemians on economic growth, we apply an instrumental variable approach using as an exogenous instrument the geographic distribution of bohemians prior to the Industrial Revolution in Germany. This distribution was primary the result of competition for prestige between courts and not of economic prosperity. Accordingly, the instrument is independent of today's regional economic development. Focusing on the concentration of highly skilled people today that is explained by the proximity to exogenous concentrations of bohemians, the observed local average treatment effect supports the hypothesis of a positive impact of bohemians on regional economic development.
Keywords: R11; J24; C31; 330; regional growth; human capital; bohemians; instrumental variables; Regionales Wachstum; Humankapital; Hochqualifizierte Arbeitskräfte; Regionale Disparität; Regionale Entwicklung; Industrialisierung; Wirtschaftsgeschichte; Deutschland (bis 1945)